Theoretical and experimental investigation of the Miller cycle diesel engine in terms of performance and emission parameters - Gonca, Guven; Sahin, Bahri; Parlak, Adnan; Ust, Yasin; Ayhan, Vezir; Cesur, Idris; Boru, Baris (ELSEVIER SCI LTD, 2015)
Pollutant exhaust emissions, particularly NOx, produced by diesel engines must be reduced to limit values defined by the environmental regulations as the emissions have many harmful influences on the environment. Recently, the application of the Miller cycle into the internal combustion engines has been proposed to abate NOx emissions. In the present study, the Miller cycle with late intake valve closing (LIVC) version is applied into a single cylinder, four-stroke, direct injection, naturally aspirated diesel engine. Three different cam shafts have been manufactured to provide 5, 10 and 15 crank angle (CA) retarding compared to original camshaft. The optimum retarding angle has been determined as 5 CA in terms of NOx reduction. The attained results have been compared with conventional diesel engine which has standard CA (0 crank angle retarding) in point of the performance and NO, HC, CO emissions. In order to provide a model validation for engine torque, brake power, brake efficiency, specific fuel consumption (SFC) and NO, the Miller cycle diesel engine is modeled by using two-zone combustion model for 5 CA retarding at full load conditions. The simulation results have been verified with experimental data with non-considerable errors. In the experimental results, NO emissions decreased by 30% with 2.5% power loss and a remarkable change is not seen in the HC, CO emissions. The results show that the method could be easily applied into the diesel engine in order to minimize NO emissions. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Diesel engine; Miller cycle; Performance; Emission; Two-zone combustion model; STEAM INJECTION; NO EMISSIONS; EFFICIENCY; IMPROVEMENT; Energy & Fuels; Engineering